Analisa Efektifitas Pembelajaran Bahasa Inggris antara Metode In-Class dengan Metode Self Learning dengan Media Komputer - Setyorini, Ari (Humaniora, 2011)
The purpose of this study was to measure the effectiveness of learning English between the methods in-class with a method of self-learning using computer aids and operational support staff in an international school.  The research method used is descriptive method with a final score comparing between learning results and analyze how the increased English proficiency. A gap still exists in terms of English language proficiency for the operational support staff, we conducted this training program in the classroom with instructors as mentors and teachers in the learning process. And due to busy work schedules and shift changes are different, this learning program made independently by using a computer. The participants who experienced an increase in value is only one person or 6.67%. With these results it may be concluded that a training program with the guidance of instructors in the classroom are more effective and successful in providing a better ability than the self-learning program with the help of computers. Things that affect, among others, are motivation to learn, as seen from the low frequency of attendance at the laboratory (average 93.33% attendance below the required number of attendance), for participants with secondary education level and lower, self-study programs does not seem to be effective, and computer media can not replace the function of a mentor or teacher.